2010
DOI: 10.1016/j.conb.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Shedding new light on the role of the basal ganglia-superior colliculus pathway in eye movements

Abstract: SUMMARY A large body of work spanning 25+ years provides compelling evidence for the involvement of the basal ganglia-superior colliculus pathway in the initiation of rapid, orienting movements of the eyes, called saccades. The role of this pathway in saccade control is similar to the role of the basal ganglia-thalamic pathway in the control of skeletal movement: a transient cessation in tonic inhibition supplied by the basal ganglia to motor structures releases movements via the direct pathway whereas a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 82 publications
1
41
0
3
Order By: Relevance
“…Others have suggested that spontaneous fluctuations in the DMN (Ramot et al 2011) are correlated with oculomotor signals during eyes closed. Instead, we observed prominent subcortical activations, in agreement with neurophysiological evidence suggesting a prominent role of basal ganglia in self-generated eye movements (Shires et al 2010;Utter and Basso 2008). Furthermore, the study by Ramot et al (2011) included BOLD effects that exceeded a low, uncorrected statistical threshold despite the study having a large number of participants, suggesting that the size of the eye movement effects on cortical BOLD signals was rather small.…”
Section: Discussionsupporting
confidence: 87%
“…Others have suggested that spontaneous fluctuations in the DMN (Ramot et al 2011) are correlated with oculomotor signals during eyes closed. Instead, we observed prominent subcortical activations, in agreement with neurophysiological evidence suggesting a prominent role of basal ganglia in self-generated eye movements (Shires et al 2010;Utter and Basso 2008). Furthermore, the study by Ramot et al (2011) included BOLD effects that exceeded a low, uncorrected statistical threshold despite the study having a large number of participants, suggesting that the size of the eye movement effects on cortical BOLD signals was rather small.…”
Section: Discussionsupporting
confidence: 87%
“…saccade choice, and content valuation (76). On the other hand, the neuronal activity in the early time window also could be affected by early emotional and motivational activity.…”
Section: Discussionmentioning
confidence: 99%
“…Increased SNR neuronal activity has been associated with normal limb movement [17] and cessation of saccadic eye movements [18]. Thus, the bursting firing pattern likely plays a role in normal physiology.…”
Section: Discussionmentioning
confidence: 99%